(untitled) (Research, Society and Development, 2021)
The aim of the present study was to develop chickpea pie dough with flaxseed flour and to evaluate its microbiological, sensory and nutritional characteristics. Standard Formulation (FP), based on refined wheat flour, and Experimental Formulation (FE), based on chickpeas with flaxseed flour, were developed. Microbiological and sensory analyzes and nutritional information were performed on the stuffed baked pasta. Acceptance and purchase intention tests were applied. FP and FE were in accordance with the current legal microbiological standards. There was a difference (p≤0.05) between FP and FE for all attributes; however, with averages > 7, indicating good acceptance. Compared to FP, FE obtained lower averages of texture and flavor, but well accepted, and 52% of consumers would buy FE. The FE contains lower levels of total and saturated fats, sodium and energy value, and higher proteins, compared to FP, and with 5.6g of food fibers. Chickpeas and flaxseed flour are viable for pie dough with added sensory, nutritional and functional values and market potential.